An Irrigation Suction System Using a Pressurized Fluid High-Flow Pump System in Comparison with a Standard Cuff Pressure System: Technical Note - Murai, Yasuo; Matano, Fumihiro; Toda, Shigeki; Kobayashi, Shiro; Morita, Akio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective In neurosurgical operations, such as clipping of ruptured cerebral aneurysms, irrigation of the operative field is a basic and extremely important surgical technique. Various irrigation-suction (IS) systems have been marketed for irrigation of operative fields in neurosurgery. However, with these devices, we often must increase the cuff pressure to maintain fluid power and change the fluid bag relatively frequently. We report the usefulness of pressurized irrigation fluid with the Niagara high-flow irrigation system (NI).Method Using both the NI system and an IS, we altered pressure and duration to investigate differences in flow rate.Results There was no change in flow rate 80 minutes after pressurization of the NI system, and flow rates decreased slightly. Additionally, flow rates using NI were sensitive to changes in pressure.Conclusion This system has reduced the workload of assisting nurses and surgeons during surgery. Thus we consider the technique to be very useful for neurosurgical operations that require delicate procedures.
Keywords: flow volume; irrigation; suction; microsurgery